2019
DOI: 10.1155/2019/9059761
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Events and Carotid Atherosclerosis: A 5-Year Prospective Cohort Study in Patients with Type 2 Diabetes and a Contemporary Cardiovascular Prevention Treatment

Abstract: Background and Aims. European recommendations on cardiovascular prevention suggest that carotid atherosclerosis assessment by duplex ultrasonography could help in some cases to better assess CV risk. We investigated whether the presence of carotid atherosclerosis determined by duplex ultrasonography is associated with cardiovascular events in patients with type 2 diabetes and could therefore help to reclassify cardiovascular risk. Methods. Among 624 consecutive patients with type 2 diabetes and carotid atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Male predominance in the present study was also found by other authors 17,19,20 . In a study conducted by Herinirina et al in a general Malagasy population, male gender was a determining factor in the increase in common carotid intima‐media thickness ( p value = .008) 24 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Male predominance in the present study was also found by other authors 17,19,20 . In a study conducted by Herinirina et al in a general Malagasy population, male gender was a determining factor in the increase in common carotid intima‐media thickness ( p value = .008) 24 .…”
Section: Discussionsupporting
confidence: 88%
“…This was superimposable on the findings of French studies in which 65.4% of a diabetic population presented with carotid atherosclerosis and the proportion of stenoses <50% and ≥50% were 64.6% and 4.1%, respectively. 17 , 19 However, in other Chinese and Korean studies found lower prevalence ranging from 30.8% to 45%. 20 , 21 , 22 In the study by Yang et al, 82.25% of patients had ≤49% stenosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is characterized by three pathological and anatomic stages, including the initial stage, progressive stage, and terminal stage [ 17 ]. CAS plaque rupture or erosion is a high-risk factor for cardiovascular disease and accounts for most deaths in CAS patients [ 18 , 19 ]. Transcriptomic sequencing (RNA-seq) is a highly useful tool for studying gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the gold standard for monitoring blood glucose levels is blood HbA1c concentration and this has been proved to be an independent marker for cardiovascular disease risk [8]. However, HbA1c can be influenced by the presence of drugs, ethnicity, and other factors.…”
Section: Discussionmentioning
confidence: 99%